Hepatotoxic Effects of Methanol Leaf Extract of Chromolaena odorata on Liver Biomarkers and Histology in Wistar Rats - Tologbonse, Adedoyin A.; Onwuka, Ngozi A.; Otimanam, Hillary E.; Ukah, Armstrong C.; Omeluko, Mmaduabuchi N.; Abam, Ejika I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2026)
Background: Chromolaena odorata plant is widely used in traditional medicine for treating various ailments, including diabetes, malaria, wounds, gastrointestinal disorders and inflammation. This study was designed to determine the effect of C. odorata on Liver biomarkers and the histological architecture integrity of the liver in Wistar rat models. Methods: Matured Wistar rats 180 g – 200 g were divided into four groups of five animals each. The rats were administered with C. odorata methanol extracts via oral route for 28 days consecutively and all animals were utilized in the in-vivo studies. Standard liver function tests were done using colorimetric method for determination of specific enzymes/biomarkers. Histological analysis was performed on the harvested liver using Mayer’s hematoxylin and eosin staining techniques. Results: The findings showed reduction in the total bilirubin, ALT and AST while the levels of ALP and direct bilirubin increased. This is suggestive of a potential hepatoprotective effect of the extract at moderate doses and hepatic dysfunction or membrane leakages at a high dose (821.58 mg/Kg), these results were significant at p ? 0.05–0.01 when compared with the control. Histological findings suggest that low doses were safe. Conclusion: The extract exhibited dose-dependent hepatotoxic effects on liver enzymes. Low doses are safe, while higher doses induced a moderate altered hepato-architecture with areas of degenerated hepatic and ductal cells, indicating a need for careful dose optimization. These findings validate the traditional use of C. odorata in treatmet of gastrointestinal disorders and suggest its potential as a natural therapeutic agent.